Verbal Semantics Drives Early Anticipatory Eye Movements during the Comprehension of Verb-Initial Sentences - Sauppe, Sebastian (Frontiers in Psychology, 2016)
Studies on anticipatory processes during sentence comprehension often focus on the prediction of postverbal direct objects. In subject-initial languages (the target of most studies so far), however, the position in the sentence, the syntactic function, and the semantic role of arguments are often conflated. For example, in the sentence "The frog will eat the fly" the syntactic object ("fly") is at the same time also the last word and the patient argument of the verb. It is therefore not apparent which kind of information listeners orient to for predictive processing during sentence comprehension. A visual world eye tracking study on the verb-initial language Tagalog (Austronesian) tested what kind of information listeners use to anticipate upcoming postverbal linguistic input. The grammatical structure of Tagalog allows to test whether listeners' anticipatory gaze behavior is guided by predictions of the linear order of words, by syntactic functions (e.g., subject/object), or by semantic roles (agent/patient). Participants heard sentences of the type "Eat frog fly" or "Eat fly frog" (both meaning "The frog will eat the fly") while looking at displays containing an agent referent ("frog"), a patient referent ("fly") and a distractor. The verb carried morphological marking that allowed the order and syntactic function of agent and patient to be inferred. After having heard the verb, listeners fixated on the agent irrespective of its syntactic function or position in the sentence. While hearing the first-mentioned argument, listeners fixated on the corresponding referent in the display accordingly and then initiated saccades to the last-mentioned referent before it was encountered. The results indicate that listeners used verbal semantics to identify referents and their semantic roles early; information about word order or syntactic functions did not influence anticipatory gaze behavior directly after the verb was heard. In this verb-initial language, event semantics takes early precedence during the comprehension of sentences, while arguments are anticipated temporally more local to when they are encountered. The current experiment thus helps to better understand anticipation during language processing by employing linguistic structures not available in previously studied subject-initial languages.